Effects of intradialytic exercise on frailty in maintenance hemodialysis patients: a systematic review and meta-analysis - Zou, Zhao Hua; Zhang, Ji Quan; Yi, Zi Han; Chen, Xing; Qing, Wei (Frontiers in Physiology, 2025)
BackgroundThe pooled prevalence of frailty in maintenance hemodialysis patients is increasing, and research on the effects of intradialytic exercise to improve frailty remains limited.ObjectivesTo analyze the effects of intradialytic exercise on frailty in maintenance hemodialysis patients through randomized clinical trials and quasi-experimental studies.MethodsWe performed a comprehensive literature search in PubMed, Embase, Web of Science, and Cochrane Library, and English-language publications were indexed from January 2010 to August 2024. Statistical analyses were performed using Review Manager V.5.3 and STATA 15.0. Statistical heterogeneity among studies was quantified using the Chi-square and I-square tests, and publication bias was evaluated using Egger’s test and funnel plots.Results31 studies involving 1,365 maintenance hemodialysis patients were included. The data from the meta-analysis showed that intradialytic exercise significantly reduced frailty score (MD = −0.98, 95%CI: 1.90 to −0.06, p = 0.04) and fatigue (SMD = −0.47, 95%CI: 0.72 to −0.23, p = 0.0001). Also, intradialytic exercise significantly increased grip strength (MD = 2.42, 95%CI:0.78 to 4.06, p = 0.004), 6-min walking distance (MD = 36.65, 95%CI:24.90 to 48.39, p < 0.0001), and step counts (SMD = 0.32, 95%CI:0.04 to 0.60, p = 0.03). However, no significant effects were found in body weight (MD = 0.71, 95%CI: 1.28 to 2.69, p = 0.48).ConclusionIntradialytic exercise can significantly improve overall frailty and frailty indicators such as grip strength, 6-min walking distance, step counts, and fatigue. Thus, intradialytic exercises might be a viable strategy for frailty in maintenance hemodialysis patients.Systematic Review registrationCRD42024576582.